Crustal and Upper Mantle Density Structure Beneath the Qinghai-Tibet Plateau and Surrounding Areas Derived from EGM2008 Geoid Anomalies - Honglei Li; Jian Fang (ISPRS International Journal of Geo-Information, 2016)
As the most active plateau on the Earth, the Qinghai-Tibet Plateau (TP) has a complex crust–mantle structure. Knowledge of the distribution of such a structure provides information for understanding the underlying geodynamic processes. We obtain a three-dimensional model of the density of the crust and the upper mantle beneath the TP and surrounding areas from height anomalies using the Earth Gravitational Model 2008 (EGM2008). We refine the estimated density in the model iteratively using an initial density contrast model. We confirm that the EGM2008 products can be used to constrain the crust–mantle density structures. Our major findings are: (1) At a depth of 300–400 km, high-D(ensity) anomalies terminate around the Jinsha River Suture (JRS) in the central TP, which suggests that the Indian Plate has reached across the Bangong Nujiang Suture (BNS) and almost reaches the JRS. (2) On the eastern TP, low-D(ensity) anomalies at a depth of 0–300 km and with high-D anomalies at 400–670 km further verified the current eastward subduction of the Indian Plate. The ongoing subduction process provides force that results in frequent earthquakes and volcanoes. (3) At a depth of 600 km, low-D anomalies inside the TP illustrate the presence of hot weak material beneath it, which contribute to the inward thrusting of external material.